2006
DOI: 10.1038/sj.emboj.7600925
|View full text |Cite
|
Sign up to set email alerts
|

Lsh is involved in de novo methylation of DNA

Abstract: Deletion of Lsh perturbs DNA methylation patterns in mice yet it is unknown whether Lsh plays a direct role in the methylation process. Two types of methylation pathways have been distinguished: maintenance methylation by Dnmt1 occurring at the replication fork, and de novo methylation established by the methyltransferases Dnmt3a and Dnmt3b. Using an episomal vector in LshÀ/À embryonic fibroblasts, we demonstrate that the acquisition of DNA methylation depends on the presence of Lsh. In contrast, maintenance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
130
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(139 citation statements)
references
References 48 publications
8
130
0
1
Order By: Relevance
“…Among them, Lsh (lymphoid-specific helicase) is a member of the SNF2 family of chromatin remodeling ATPases that facilitates the access of Dnmts to the DNA substrate (Zhu et al, 2006). Inactivation of Lsh in mice results in decreased methylation and increased expression of IAP elements in female germ cells and in embryonic tissues, which leads to early post-natal lethality (Huang et al, 2004;De La Fuente et al, 2006).…”
Section: Host Responses To Tes or How To Live With A Herd Of Squattersmentioning
confidence: 99%
“…Among them, Lsh (lymphoid-specific helicase) is a member of the SNF2 family of chromatin remodeling ATPases that facilitates the access of Dnmts to the DNA substrate (Zhu et al, 2006). Inactivation of Lsh in mice results in decreased methylation and increased expression of IAP elements in female germ cells and in embryonic tissues, which leads to early post-natal lethality (Huang et al, 2004;De La Fuente et al, 2006).…”
Section: Host Responses To Tes or How To Live With A Herd Of Squattersmentioning
confidence: 99%
“…It has been also confirmed that DNMT3L aids the de novo methyltransferases by maximizing their ability to bind to DNA and stimulates their activity (Goll et al, 2006). Even though the identification of the enzymes responsible for methylation patterns are now known, the exact molecular mechanisms and important cofactors that aid efficient enzymatic activity to the right sites, remain poorly understood (Zhu et al, 2006).…”
Section: De Novo Methylationmentioning
confidence: 99%
“…Consequently, maintenance methylation activity is found in all somatic cells while the maximum de novo methylation activity is found in embryonic cell lines, germ cells, or in post-implantation embryos (Zhu et al, 2006).…”
Section: Dna Methylationmentioning
confidence: 99%
See 2 more Smart Citations